Intentional spiritual care for sick children: A beacon for decreasing stress and nurturing spirituality. Issue 4 (2nd October 2021) - Harris, Kathleen I.
ABSTRACT: Every family who enters a hospital is on a personal journey. The awareness of that particular journey allows us to make more intentional and purposeful choices about how health and medical professionals want to be spiritually involved with each child and family. Spiritual care for sick children raises an important concern for health and medical professionals. The purpose of this article is to introduce the role of children's spirituality in administering intentional spiritual care for the hearts, minds, and spirits of sick children and their families in health care settings. Characteristics and principles of intentional spiritual care are discussed along with a variety of activities and interventions healthcare professionals can use effectively when taking care of the spiritual needs of young patients in hospitals. By conducting an ethnographic research study and collecting data as a participant-observer, the author documented activities with hospitalised children and how medical personnel nurtured and supported their spiritual domain.